The dependence of barrier height on temperature for Pd Schottky contacts on ZnO - Mtangi, W.; Auret, F.D.; Nyamhere, C.; Janse van Rensburg, P.J.; Chawanda, Albert; Diale, M.; Nel, J.M.; Meyer, W.E. (Elsevier, 2016)
Temperature dependent current–voltage (I–V) and capacitance–voltage (C–V) measurements have been performed on Pd/ZnO Schottky barrier diodes in the range 60–300 K. The room temperature values for the zero bias barrier height from the I–Vmeasurements (ΦI–V) was found to be 0.52 eV and from the C–V measurements (ΦC–V) as 3.83 eV. From the temperature dependence of forward bias I–V, the barrier height was observed to increase with temperature, a trend that disagrees with the negative temperature coefficient for semiconductor material. The C–V barrier height decreases with temperature, a trend that is in agreement with the negative temperature coefficient of semiconductor material. This has enabled us to fit two curves in two regions (60–120 K and 140–300 K). We have attributed this behaviour to a defect observed by DLTS with energy level 0.31 eV below the conduction band and defect concentration of between 4×1016 and 6×1016 cm−3 that traps carriers, influencing the determination of the barrier height.